Letermovir Prophylaxis for Cytomegalovirus Infection in Allogeneic Stem Cell Transplantation: A Real-World Experience - Martino, Massimo; Pitino, Annalisa; Gori, Mercedes; Bruno, Benedetto; Crescimanno, Alessandra; Federico, Vincenzo; Picardi, Alessandra; Tringali, Stefania; Ingrosso, Claudia; Carluccio, Paola; Pastore, Domenico; Musuraca, Gerardo; et al. (Frontiers in Oncology, 2021)
Despite effective treatments, cytomegalovirus (CMV)continues to have a significant impact on morbidity and mortality in allogeneic stem cell transplant (allo-SCT) recipients. This multicenter, retrospective, cohortstudy aimed to evaluate the reproducibility of the safety and efficacy of commercially available letermovir for CMV prophylaxis in a real-world setting. Endpoints were rates of clinically significant CMV infection (CSCI), defined as CMV disease or CMV viremia reactivation within day +100-+168. 204 adult CMV-seropositive allo-SCT recipients from 17 Italian centers (median age 52 years) were treated with LET 240 mg/day between day 0 and day +28. Overall, 28.9% of patients underwent a haploidentical, 32.4% a matched related, and 27.5% a matched unrelated donor (MUD) transplant. 65.7% were considered at high risk of CSCI and 65.2% had a CMV seropositive donor. Low to mild severe adverse events were observed in 40.7% of patients during treatment (gastrointestinal toxicity (36.3%) and skin rash (10.3%)). Cumulative incidence of CSCI at day +100 and day +168 was 5.4% and 18.1%, respectively, whereas the Kaplan-Meier event rate was 5.8% (95% CI: 2.4-9.1) and 23.3% (95% CI: 16.3-29.7), respectively. Overall mortality was 6.4% at day +100 and 7.3% at day +168. This real-world experience confirms the efficacy and safety of CMV.